Differential expression of interleukin‐2 by anti‐CD3‐stimulated peripheral blood mononuclear cells in patients with psoriatic arthritis and patients with cutaneous psoriasis. (13th November 2013) - Bosè, F.; Capsoni, F.; Molteni, S.; Raeli, L.; Diani, M.; Altomare, A.; Garavaglia, M.; Garutti, C.; Frigerio, E.; Banfi, G.; Altomare, G.; Reali, E.
Summary The differences in systemic T‐cell responses between patients with psoriatic arthritis (PsA) and patients with cutaneous psoriasis (Ps) are still largely unknown. To determine differential features that could be used to distinguish PsA from Ps, we compared the cytokine secretion profile of circulating T cells in patients with PsA, patients with cutaneous Ps and control subjects. We determined Th1, Th2 and Th17 cytokine secretion of anti‐CD3‐stimulated peripheral blood mononuclear cells (PBMCs) using a cytokine bead array. Normality of data distribution was assessed by the Shapiro–Wilk test, and statistical significance was calculated by the Mann–Whitney test. Phenotypic characterization of circulating T cells was performed by fluorescence‐activated cell sorting analysis. We found that the major systemic differences distinguishing PsA from cutaneous Ps were the increased secretion of interleukin (IL)‐2 by α‐CD3‐stimulated PBMCs and a higher percentage of circulating CD3+ T cells expressing the proliferation marker CD71 in PsA. These results indicate IL‐2 as a possible biomarker of PsA, and suggest a role of circulating T cells with high proliferative capacity in the pathogenesis of PsA.